The Physical and Morphological Characteristics of Mango Powder (Mangifera indica L. cv Tommy Atkins) Produced by Foam Mat Drying - Chaux-Gutiérrez, Ana María [UNESP]; Pérez-Monterroza, Ezequiel José [UNESP]; Telis, Vânia Regina Nicoletti [UNESP]; Mauro, Maria Aparecida [UNESP] (Springer Nature, 2017)
The thermal behavior, moisture adsorption properties and structural and morphological characteristics of mango powders were evaluated. The powders were obtained by foam mat drying methodology using albumin (ALB), mixture (EB) of monoglycerides of fatty acids, sorbitan monostearate and polyoxyethylene sorbitan monostearate and a combination of the two (EB-ALB) as foaming agents. The evaluation was done by differential scanning calorimetry (DSC), X-ray diffraction (XRD) and scanning electron microscopy (SEM), and the moisture adsorption isotherms were also determined. The powder with EB had a glass transition temperature (Tg) of −4.2 °C. The denaturation temperature of pure albumin (82.2 °C) increased in the powders with ALB to 117 °C and in those with EB-ALB to 102 °C, due to the thermal stability provided by the pulp sugars. The moisture sorption isotherm of the EB-powder showed a higher water equilibrium content than the other powders. All the powders were in the amorphous state. The morphology of the powder with EB showed corrugated particles, whereas those with ALB and EB-ALB showed particles with a less porous aspect and more compact surfaces than the powders with EB.
Keywords: Albumin; Emulsifier; Glass transition temperature; Moisture adsorption; Sorbitan monostearate; X-ray diffraction